Angiotensin II rapidly increases phosphatidate-phosphoinositide synthesis and phosphoinositide hydrolysis and mobilizes intracellular calcium in cultured arterial muscle cells. - Smith, J B (1984)
Smooth muscle cells were cultured from rat thoracic aorta and labeled to a stable specific activity with 45Ca2+, myo-[2-3H]inositol, or 32Pi. The efflux of 45Ca2+ was monitored over 10-sec intervals. Angiotensin II (AII) increased the amount of 45Ca2+ lost by 5-fold in the first 10-sec interval after the addition of AII and by 10-fold in the second 10-sec interval. AII-stimulated 45Ca2+ release was blocked by the angiotensin antagonist [1-sarcosine, 8-leucine]AII and by La3+. The removal of external Ca2+ had no effect on AII-stimulated 45Ca2+ release. Depolarization with high external K+ only slightly increased 45Ca2+ efflux and had no effect on AII-induced 45Ca2+ release. AII had no effect on the initial rate of 45Ca2+ influx. These results indicate that the rapid 45Ca2+ efflux evoked by AII is probably due to the release of 45Ca2+ sequestered intracellularly rather than to an increase in the Ca2+ permeability of the plasma membrane. AII provoked rapid increases in the levels of phosphatidic acid and phosphoinositides in the cells. These increases in phospholipids were associated with increases in phospholipase C-generated inositol phosphates (tri-, di-, and mono-). It appears that AII simultaneously increases phosphoinositide hydrolysis and synthesis in vascular smooth muscle, and both phospholipid effects may contribute to inositol triphosphate generation, which was sufficiently rapid to have a role in intracellular Ca2+ mobilization.